O processo de investigação de acidentes de trabalho para instauração de ações regressivas pela Advocacia-Geral da União: análise dos principais aspectos facilitadores e dificultadores - Armando, Aníbal César Resende Netto (2016)
The purpose of the study is to analyze the regressive actions related accidents in cases of granting social security benefits for workplace accidents in which the employer is to blame for the misfortune. In this context, this study was aimed to analyze the main factors that influence positively or negatively the process of investigation and analysis of accidents for the introduction of regressive actions by Attorney General of the Union, in the role of legal representative of the National Institute of Social Security. The methodology for the development of the present work involves bibliographical, documental and field research. It has information about the regressive actions, work accidents, social security, National Security Policy and Health at Work, as well as records related to workplace accidents, accident benefits, regressive actions and inspection activities, in addition to public workers’ perceptions about the analyzed issue. As a result, the positive influence factor was the preparation of the report produced by the Fiscal Auditors of Labor and as thenegative influence factor was the lack of conditions and structure of workplace supervision organs in Brazil.